The History of the Entry of Islam in the Land of Karo - Diah Syahfitri Chan; Suprayitno; Nursukma Suri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research investigates the history of the introduction of Islam in Tanah Karo, a region rich in cultural and historical heritage in Indonesia. Against the backdrop of religious and cultural diversity in Tanah Karo, this research aims to answer the question of how Islam entered and developed in Karo society. The research method used includes a historical study with analysis of literature, archives, and other primary sources. The results revealed that Islam entered Tanah Karo through various channels, including trade and dissemination by ulama. The process of Islam entry was influenced by the social, political and cultural context of Karo society at the time. The conclusion of this study is that the entry of Islam in Tanah Karo was the result of a complex interaction between internal and external factors, and became an integral part of the historical development and cultural identity of the Karo people.